Auxis thazard - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Auxis thazard (Lacepède, 1800). Frigate Tuna . To 61 cm (24 in) TL (Miller and Lea 1972). Circumglobal; Huntington Beach (Personal communication: Los Angeles County Museum of Natural History Fish Collection, Los Angeles, California), and Santa Catalina Island, southern California to Chile (Pequeño 1989), including Gulf of California (Robertson and Allen 2015) and Islas Galápagos (Miller and Lea 1972). The record of this species from the southern Kuril Islands in Savinykh (1998) appears to be in error and was changed to Auxis rochei in Parin (2003). Neritic and oceanic epipelagic; depth: surface to 200 m (656 ft) (Robertson and Allen 2002). The eastern Pacific form is recognized as the subspecies Auxis thazard brachydorax Collette and Aadland 1996 (Collette 2003). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 211, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008